(untitled) (American Journal of Islam and Society, 2009)
In his capacity as president of the Islamic Republic of Pakistan, on 13 April 2009AsifAli Zardari signed an ordinance (Nizam-e-Adl Regulation) imposing Shari`ah law on the Swat Valley. Although approved by the Pakistani National Assembly,1 analysts believe this measure will embolden the Taliban’s already increasing strength in and around that region. Some human right groups also fear that the Taliban will see this decision as a license to send the region’s people back to the “Dark Ages" (whatever that may mean).2 These reactions are not new. It may be quite tempting to ask why the Shari`ah is so abhorrent to its opponents and why implementing it is so attractive to those Muslims who are bent on applying it. Frankly put, although the mere mention of such a prospect evokes both emotions, to the majority of practicing Muslims even posing such questions affronts their religious sensibilities. However, is the current reaction truly about the Shari`ah’s essence and application, or about what the Taliban will make of it? Yes, the maddening and egregious behavior of the Taliban and other extremist elements render almost everything about Islam (especially the Shari`ah) terrifyingly repulsive. But in this era of information explosion, it is the responsibility of the world’s “civilized” people, regardless of religion, to inform themselves, in an honest and sincere manner, about the Shari`ah’s contents (not that doing so would absolutely guarantee its positive or fair consideration) in order to avoid any “hair-splitting” whenever its application is proposed.Whose fault is it if people fail to distinguish between the likes of the Taliban (who are unable to understand the Shari`ah’s real reasons and wisdom, even if they have the utmost zeal to apply them) and the actual Shari`ah (which, the majority ofMuslims believe, exists only to protect and guide people in their lives and does not impose on them anything beyond their capability)? ...